Pengembangan Kawasan Permukiman Daerah Sub-urban Moncongloe Berbasis Analisis Faktor-faktor yang Berpengaruh - Mursaling Mursaling; Arifuddin Akil; Ihsan Ihsan (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2019)
The increasing need for residential space in Makassar City has resulted in suburban areas such as the Moncongloe Subdistrict, Maros Regency being the area of ​​choice to meet the need for space. Seeing these conditions, it is necessary to develop an appropriate settlement in the District of Moncongloe. The purpose of this study is to determine the characteristics of population, land use and road network, factors that influence settlement development, and direction of settlement development based on factor analysis in Moncongloe District, specifically Moncongloe Lappara Village and Moncongloe Village. The analytical method used is regression analysis, spatial analysis, and comparative analysis. The results showed that the function of the building was quite diverse with linear and concentric patterns, the main road network connecting Moncongloe with Maros Regency, Gowa Regency, and Makassar City. Factors affecting the development of settlements in the Village of Moncongloe Lappara and the Village of Moncongloe include the availability of facilities and population development. The priority locations suggested in the development of settlements in Moncongloe Lappara Village and Moncongloe Village are, part of Panaikang Hamlet and Pammanjengan Hamlet of Moncongloe Village and parts of Mangempang and Ballapati Hamlet of Moncongloe Lappara Village. Based on the factors, the directions obtained are realizing the availability of public transportation and clean water facilities and improving the quality of the road network, flood management, and socialization related to planning documents.